2015
DOI: 10.1039/c5cp03027g
|View full text |Cite
|
Sign up to set email alerts
|

A Cu(111) supported h-BN nanosheet: a potential low-cost and high-performance catalyst for CO oxidation

Abstract: A Cu(111) supported h-BN nanosheet (h-BNNS) has been systematically investigated by first-principles DFT using dispersion corrections. During the interaction between Cu and h-BNNS, the electrons migrate from the metal to the h-BNNS, leading to the formation of gap states above and under the Fermi level. Significant electrons are observed to migrate from the supported h-BNNS to the O2 molecule, resulting in the activation of the adsorbed O2. While for the unsupported h-BNNS, the absorbed O2 is almost intact wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 60 publications
(125 reference statements)
2
31
0
Order By: Relevance
“…It is believed that bare BNNS without doping can also be catalytically active with the support of Ni (111), where Ni (111) substrate can greatly enhance the adsorption of O 2 , OOH, OH, and O on BN/Ni (111) . Similar first‐principles DFT modeling also indicated that BNNS on Cu (111) can be an efficient catalyst for CO oxidation …”
Section: Applicationsmentioning
confidence: 82%
“…It is believed that bare BNNS without doping can also be catalytically active with the support of Ni (111), where Ni (111) substrate can greatly enhance the adsorption of O 2 , OOH, OH, and O on BN/Ni (111) . Similar first‐principles DFT modeling also indicated that BNNS on Cu (111) can be an efficient catalyst for CO oxidation …”
Section: Applicationsmentioning
confidence: 82%
“…[10][11][12] Recent theoretical investigations have also suggested that metal-supported nanosheets of h-BN might be active for both CO oxidation and oxygen reduction reaction (ORR). 13,14 Indeed, the combined experimental and theoretical study of Uosaki et al demonstrated that h-BN supported on Au(111) surface has much better catalytic activity for ORR than a pure Au(111) electrode. 2 These authors suggested that defective h-BN nanosheets with edge sites play an important role in the ORR.…”
Section: Introductionmentioning
confidence: 99%
“…This barrier is lower as compared to metal-doped catalysts (such as M-BN (M = Co)). [47,48] M-PMA (M = Pt, Fe, Ir, Rh, Ru,Cu(111) and Ni(111))), [49][50][51] and lower than that of boron and nitrogen doped grapheme (0.84 eV). [52] Although the barrier of this step for Ru-embedded h-BN (0.41 eV) [45] and Pt 1 /FeO x (0.48 eV) [3] is lower, the barriers of the second oxygen transfer (0.71 and 0.77 eV) in these two systems are higher as compared to that of three silicon-doped h-BN (0.72/0.43 eV).…”
Section: The First Oxygen Transfermentioning
confidence: 99%